2014
DOI: 10.3892/br.2014.382
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography-mass spectrometry and high-performance liquid chromotagraphy analysis of the drug absorption characteristics in the buccal mucosa via a circulating device

Abstract: The aim of the present study was to investigate the characteristics of Su Xiao Jiu Xin dripping pill absorption in the buccal mucosa of healthy volunteers. This pill is a traditional Chinese medicine that is widely used as an emergency treatment for cardiovascular and cerebrovascular diseases. It is sublingually administered and can be absorbed in the buccal mucosa. In the present study, a method was developed to investigate the absorption characteristics in the buccal mucosa of healthy volunteers via a circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This result may ascribe to the physicochemistry properties of the volatile analytes. It has been reported that these five analytes can be absorbed more efficiently and rapidly because of their fat‐soluble character and smaller molecular weights (<200 Da); they all can easily pass through the buccal mucosa membrane and get into the bloodstream .…”
Section: Resultsmentioning
confidence: 99%
“…This result may ascribe to the physicochemistry properties of the volatile analytes. It has been reported that these five analytes can be absorbed more efficiently and rapidly because of their fat‐soluble character and smaller molecular weights (<200 Da); they all can easily pass through the buccal mucosa membrane and get into the bloodstream .…”
Section: Resultsmentioning
confidence: 99%
“…Without the indoor-positioning system, it is hard to find an individual at risk and nearby as soon as possible. For instance, in case an old person has a heart attack, and there is no opportunity to take a su-xiao-jiu-xin pill (this medicine may relieve a sudden heart attack), nearby, people can be informed to near him and help him to take the pill [24]. This will significantly improve the success rate of rescue.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, algae may produce compounds that give a disgusting taste and odor to water, as is the case of 2-Methyl-Isoborneol [3], which even at low concentrations can be detected by human senses [4], interfering negatively in water and beverage companies and aquaculture [5][6][7][8]. Isoborneol, a compound with a chemical structure similar to 2-methyl-Isoborneol, can be found in vegetable oils and is used in applications ranging from antiviral for herpes [9], in the treatment treatment of cardiovascular diseases [10], and as a natural repellent [11]. Therefore, the presence of these compounds in drinking water must be monitored and controlled by highly sensitive and easy handling instrumentation.…”
Section: Introductionmentioning
confidence: 99%